Development Of Inquiry Student Worksheet To Train High Order Thinking Skill (HOTS) in Reaction Rate - Khudrotunnada Firma Aditya; Ismono Ismono (Universitas Lampung, 2020)
This study aims to describe the feasibility of Students’ Worksheet using inquiry-based to train High Order Thinking Skill (HOTS) on the Reaction Rate Material. The research method used is the 4-D model (Define, Design, Develop, Disseminate), but in this study it only reaches the stage Develop. Furthermore, a limited trial was carried out on 12 students of class XI at SMAN 1 Krian. The research instrument consisted of a review sheet, a validation sheet, a response questionnaire, a test sheet for learning outcomes in the domain of knowledge and a HOTS pretets-posttest question sheet. The feasibility of Students’ Worksheet is reviewed based on 3 criteria, as the validity of the validation results by the validator, the practicality of the students' responses and the effectiveness of the learning outcomes test in the realm of knowledge and the HOTS pretest-posttest results. Data analysis using quantitative descriptive method. The results obtained showed the percentage of Students’ Worksheet validity for content, language, practicality and effectiveness criteria of 86.2%, 87.8%, 88.4% and 91.3% with very valid categories. The developed Students’ Worksheet received a very positive response with a percentage of 92.2% and was stated to be very practive. The results of the increase in HOTS of students are described by the acquisition of an n-gain score of 0.71 in the high category. Each HOTS component includes analyzing (C4) of 82.5%, evaluating (C5) of 81% and creating (C6) of 91.3% in the high category and declared effective.